Crystal structures and magnetic properties of CuX2(pdmp)2 complexes (X = Br, Cl) - Costa-Filho, Antonio J.; Munte, Claudia E.; Barberato, Claudio; Castellano, Eduarde E.; Mattioli, M. P. D. [UNESP]; Calvo, Rafael; Nascimento, Otaciro R. (American Chemical Society (ACS), 1999)
We report the synthesis and the structural and magnetic characterization of two new compounds: dibromobis-(pdmp)copper(II), CuBr2C22H24N4 (1), and dichlorobis(pdmp)copper(II), CuCl2C22H24N4 (2), where pdmp = 1-phenyl-3,5-dimethylpyrazole. The structures were refined by full-matrix least-squares techniques to R1 = 0.0620 and 0.0777, respectively. Compound 1 belongs to the space group P21/n with a = 8.165(5) Å, b = 10.432(3) Å, c = 13.385(4) Å, β = 100.12(4)̊, and Z = 2. Compound 2 belongs to the space group P21/c with a = 8.379(2) Å, b = 22.630(2) Å, c = 12.256(2) Å, β= 98.43(3)°, and Z = 4. It has the same molecular formula as a compound reported previously but a different crystal structure. Detailed single-crystal EPR measurements were performed for single-crystal samples of 1 and 2 at 9 and 35 GHz and at room temperature. The positions and line widths of the EPR lines were measured as a function of the magnetic field orientation in three orthogonal planes. The data were used to study the electronic properties of the copper ions and to evaluate the exchange interactions between them. Our results are discussed in terms of the electronic pathways for superexchange between copper ions, which are provided by the stacking of pyrazole and phenyl rings of neighboring molecules and by hydrogen-halogen bonds. © 1999 American Chemical Society.